Math trails in mathematics education: A systematic literature review on contextual learning, student engagement, and spatial reasoning (2013 – 2025) - Muhammad Ainun Niam; Musthofa Musthofa (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
Mathematics education has faced persistent challenges in student engagement, spatial reasoning, and real-world relevance. Among innovative approaches, math trails have emerged in the last decade to integrate contextual, spatial, and technology-enhanced learning experiences. This study presents a systematic review (2013–2025) examining how math trails contribute to contextual learning, enhance student engagement, and develop spatial reasoning skills. Following PRISMA 2020 guidelines, 50 relevant peer-reviewed studies were identified via Boolean searches in major databases (Scopus, ERIC, SpringerLink, MDPI, etc.) and analyzed using thematic synthesis. Three major themes were identified. First, math trails situate mathematics in authentic contexts, linking mathematical ideas to real environments and encouraging students to model real-world situations. Second, math trails promote active, collaborative learning that increases student interest and participation. Third, math trails improve spatial reasoning through tasks involving navigation, measurement, and visual-spatial problem-solving in outdoor settings. The literature goes on to say that using mobile apps and tasks that are relevant to students' cultures can improve math trails when they are used with clear learning goals and reflection. Overall, the findings suggest that math trails are a multidimensional pedagogical approach that bridges theory and practice, yielding both cognitive and affective benefits. Future research should investigate long-term impacts, cross-context adaptations, and scalable models for broader classroom adoption.